A regenerator-based thermoacoustic electricity generator with different configurations for rural communities of South Sudan country - Kisha, Wigdan (2020)
This Ph.D. thesis explores different configurations of a low-cost air-filled thermoacoustic engine for waste heat recovery and electricity generation built by the SCORE consortium. The previously tested prototypes are limited to 12.6 W maximum output from 2.5 kW heat from a biomass stove. The maximum achievable electricity output from the unpressurised air-filled system has long been a question of great interest in a wide range of thermoacoustic fields. Therefore, the aim is to push the limit of the unpressurised air-field thermoacoustic systems by enhancing the power amplification without changing the working gas, as well as the total cost due to the constraints of the application (developing world), and therefore, to meet the original 20 -100 W target set by SCORE. This was achieved by initially completing a theoretical analysis of a looped-tube thermoacoustic electricity generator of a single regenerator unit, a feedback pipe, a loudspeaker to function as electricity harvester, and a tuning stub. The engine was heated electrically. This piece of work aims to predict the likely behaviour of the acoustic wave throughout the system components by using DeltaEC modelling. Investigation of the stub pipe for phase tuning was particularly important. It was shown that a modelling procedure of a looped-tube thermoacoustic engine coupled with a power harvester and a tuning stub could be established. DeltaEC models were constructed that simulated the real prototype with all components and energy conversions taking place. The first models predicted the behaviour of the system with different load resistances of the loudspeaker, and these models have been validated experimentally. Subsequent models were developed together with experimental work to assess the influence of the stub length on the power output. This research enabled a better understanding of the wave propagation in such complex systems by using the powerful thermoacoustic tool DeltaEC. Based on this study, a more complex travelling wave thermoacoustic engine of two regenerators, a feedback pipe, two stubs, and a loudspeaker was accurately simulated. The system was optimised in two stages; the first one involved only operating conditions, while the second stage investigated geometrical aspects. The first optimisation was carried out using a novel operational methodology. This innovative technique applied asymmetric heat inputs through the engine stages while maintaining the total heat flow into the system. Asymmetric impedance distribution was observed, and this caused variation in acoustic amplification. The acoustic conditions were then improved, and a stronger wave was generated along the loop. The acoustic power was higher when the heat ratio used in the first core is smaller than that supplied into the second one. The loop acoustic power was higher by almost 18% when the heat input ratio was changed from 50%